FINANCIAL LEVERAGE AND LIQUIDITY ON GOOD CORPORATE GOVERNANCE AND STOCK RETURN - Aditya Laika Chandra; Ellen Rusliati (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2019)
Investor needed the information about financial performance in order to predict the price and return of stock. This study aims to find out the effect of financial leverage and liquidity on Good Corporate Governance (GCG) and return of stock in the manufacture companies listed in Indonesia Stock Exchange during the period of 2013-2017. The method of descriptive and verifiative are used in this study by using 94 samples determined by purposive sampling technique. A secondary data is used and analyzed by using panel data regression model and moderated regression analysis. The result showed that simultenously, financial leverage and liquidity effected negatively and significantly to the return of stock. Partially, leverage effected negatively and significantly, as well as liquidity but insignificantly. The GCG is able to moderated a simultaneous effect of financial leverage and liquidity on return of stock to be positive, but insiginificatn. However, GCG effected positively and significantly.